Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1177/105477389800700305
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Predictors of Children's Postoperative Pain

Abstract: The purpose of this study was to investigate the influence of psychosocial variables in the prediction of children's pain intensity following surgery. Forty-two children, ages 7 to 17 years (M = 12.26, SD = 3.06), completed an interview 1 week prior to surgery assessing anticipatory distress related to their forthcoming surgery and history of coping strategy use. Following surgery, children reported the intensity of their pain using visual analog scales. Findings demonstrated that the majority of children expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Patient-controlled intravenous opioid analgesia (PCA) was not commonly used for children; this treatment was frequently used by 3% (5) and sometimes by 6% (10) of all departments. Parenteral opioids were frequently used by 59% (109) of departments, and potent opioids such as morphine, ketobemidone and pethidine were never or rarely used by 15% (27). There was no signi cant correlation between the use of opioids and frequency of pain.…”
Section: Pain Treatment Methodsmentioning
confidence: 99%
“…Patient-controlled intravenous opioid analgesia (PCA) was not commonly used for children; this treatment was frequently used by 3% (5) and sometimes by 6% (10) of all departments. Parenteral opioids were frequently used by 59% (109) of departments, and potent opioids such as morphine, ketobemidone and pethidine were never or rarely used by 15% (27). There was no signi cant correlation between the use of opioids and frequency of pain.…”
Section: Pain Treatment Methodsmentioning
confidence: 99%
“…1 Research has shown that between 15%2 and 60%3–7 of children report moderate to severe acute postoperative pain (APSP). Prospective studies of pediatric APSP have shown that preoperative anticipatory anxiety, younger age, and lower anticipatory distress before surgery predict higher APSP intensity on the day of surgery,8,9 and negative affect and pessimistic expectations about surgery predict functional disability one week after oral surgery 10. In addition, studies conducted postoperatively have found that coping strategies, depression, and self-efficacy correlate with acute pain intensity scores following surgery among adolescents 11–14…”
Section: Introductionmentioning
confidence: 99%
“…Historically, there have been significant gaps in pain management in children, with less effective pain control in children as compared to adults (3). Among trainees, there is significant variation in knowledge and prescribing practices for analgesics (4).…”
Section: Introductionmentioning
confidence: 99%